Children’s Body Odors: Hints to the Development Status - Schäfer, Laura; Sorokowska, Agnieszka; Weidner, Kerstin; Croy, Ilona (Frontiers in Psychology, 2020)
Mothers can recognize their own children by body odor. Besides signaling familiarity, children’s body odors may provide other information relevant to maternal caregiving behavior, such as the child’s developmental status. Thus, we explored whether mothers are able to classify body-odors on pre- vs. postpubertal status above chance levels. In total, 164 mothers were presented with body odor samples of their own and four unfamiliar, sex-matched children who varied in age (range 0 to 18 years). Pubertal status was measured by a) determining the child’s steroid hormone level and b) parental assessment of the child’s developmental stage using the Pubertal Development Scale. Mothers classified developmental status with an accuracy of about 64%. Maternal assessments were biased towards pre-puberty. Classification was predicted by perceptual evaluation of the body odor (i.e., intensity and pleasantness) and by the child’s developmental stage, but not by hormones. In specific, mothers with pubertal-aged children classified body odors using the child’s developmental status, whereas mothers with younger children only classified body odors using perceptual information (i.e., intensity, pleasantness). Our data suggests that body odors convey developmental cues, but how this developmental information is manifested in body odor remains unclear.